Examining changes in HRV in response to varying ambient temperature. - Sollers, J.J., III (IEEE Engineering in medicine and biology magazine)
The present study is designed to examine changes in HRV in response to ambient temperature change in college-aged men and women. We hypothesize that the VLFP (very-low-frequency power) component would be increased in the cold environment whereas the HFP (high-frequency power) component would be reduced in the hot environment with no differences between baseline and the cold condition.